A Multiweek Project Examining the Chemotactic Behavior of Tetrahymena in an Undergraduate Biology Laboratory - Rachel Hongo (American Society for Microbiology, 2020)
A multi-week laboratory project has been developed to incorporate elements of student investigation, chemotactic behavior of protists, and genetic effects on chemotactic activity of Tetrahymena.  The chemotaxis assay is based on spectrophotometric detection of protist-induced light scattering as cells migrate into a density gradient containing a known attractant. The three-week project consists of an introductory chemotaxis assay, investigation of dose-response effects, and culminates with the exploration of a Tetrahymena genetic mutant with known defects in motility.  Additionally, this project incorporates a microscopic investigation of cellular structure and swimming behavior of mutant and wild-type cells.  Students have responded well to the nature of the project, displaying clear understanding of the mechanism of the assay as well as the response of the protists to environmental manipulation and the molecular defects in the mutant cells.